Prevalence of calcified triticeous cartilage-compatible images on 2500 digital panoramic radiographs of a Brazilian population sample - Soares, Guilherme Costa; Kurita, Lúcio Mitsuo; Alves, Ana Paula Negreiros Nunes; Silva, Paulo Goberlânio de Barros; Santos, Juliana Mara Oliveira; Costa, Fábio Wildson Gurgel (Journal of Health & Biological Sciences, 2020)
Objective: To investigate the prevalence of calcified triticeous cartilage (CTC)-compatible images on digital panoramic radiographs of a significant Brazilian population sample. Methods: In this retrospective study, 2500 digital panoramic radiographs were analyzed by a trained examiner using contrast and brightness adjustments of the Adobe® Photoshop® CC 2015 software. Data were collected and exported for statistical analysis (p-value <0.05 was considered statistically significant). Results: The prevalence of CTC-compatible images was 4.5% (61.1% in women and 38.9% in men). The most prevalent age ranged between 51 and 60 years (32.7%), and bilateral occurrence had a higher prevalence (46.9%). Women between the ages of 61 and 70 years showed a significantly higher prevalence of CTC-compatible images (p=0.027). Conclusion: This study showed a low prevalence of CTC-compatible images, which mainly occurred in women close to 70 years of age.